Electrical discharge in vacuum; Proceedings of the VIIth International Vacuum Congress and IIIrd International Conference in Solid Surfaces, Vienna, september 12-16, 1977; Vol. 1 - Mesyats G. A. Gennady Andreyevich (1977, 1977)
В фонде НТБ ТПУ отсутствует